Proposed program for majors in health education for the Bukidnon Normal School - Martinez, Catalina (Paculdo) 1938- (College of Education, University of the Philippines Diliman, 1968)
The study is a program proposal for majors in health education for the Bukidnon Normal School. In particular, the study is based on the health needs of elementary school pupils and the health needs of Bukidnon. The courses and experiences proposed are centered on the development of the necessary teacher and coordinator competencies on the three integral phases of Health Education, namely, Health Instruction, Healthful School Living and Health Services.